Marketing Strategy of Organic Products in Bandung: Farmer Community, Product Innovation and Social Media - Dwi Mayangsari, Ira; Ferlina Moch. Trenggana, Arlin; Salmiyah Fithrah Ali, Dini; Abdillah, Fatimah (International Journal of Engineering and Technology, 2018)
People today are more concern about a healthy life style which results in the rise of organic products demand and green awareness. This issue not only opens new opportunity to farmers but also calls them to improve their marketing strategy. This study explores a regular event from organic farmer community in Bandung, “Pasar Hejo,” in order to understand their marketing strategy that has been applied using qualitative approach. From the interview and observation, result shows the farmers join community for solidity and to expand their market, create some processed products as innovation, offer eco-tourism service and use social media application such as WhatsApp, Instagram and Facebook as their promotion tools to informing the event, and social networking to offer special price or additional discount within the event. Further, WhatsApp is used by farmers as supply chain media which communicates supply demand among farmers, agents and consumers. In addition, farmers imply that they need more supports from the government to arrange more community markets to serve consumers and educate them about healthy lifestyle. Meanwhile, consumers appreciate Pasar Hejo event which provides healthy food, entertainment, sport and education. However, they consider the price of organics products to be expensive.
Keywords: Organic Products; Community; Product Innovation; Social Media; Marketing Strategy